2021
DOI: 10.1007/s12144-021-02148-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gain-loss framing and its interaction with political ideology on social distancing and mask wearing compliance during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has caused millions of cases and over half a million deaths in the United States. While health experts urge citizens to adopt preventative measures such as social distancing and wearing a mask, these recommended behaviors are not always followed by the public. To find a way to promote preventative measures, the present study examined the role of gain-loss framing of COVID-19 related messages on social distancing and mask wearing compliance. Moreover, the study also tested potential modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In terms of income, people with highest level of income have lowest degree of compliance. Those who are seriously worried about the virus (possibly because of potential medical conditions) are more likely to wear masks ( 12 ), but people with high incomes have sufficient funds to obtain better medical care, which means that their compliance is lower. Moreover, we found that individuals with higher level of education were less likely to be compliant with wearing masks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of income, people with highest level of income have lowest degree of compliance. Those who are seriously worried about the virus (possibly because of potential medical conditions) are more likely to wear masks ( 12 ), but people with high incomes have sufficient funds to obtain better medical care, which means that their compliance is lower. Moreover, we found that individuals with higher level of education were less likely to be compliant with wearing masks.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement for assessing attitude toward adopting healthy behaviors was adapted from the research of Mir et al ( 37 ), including three items: “In my opinion, wearing a mask is an effective measure to prevent the COVID-19 pandemic,” “I will not resist wearing a mask”, and “I think wearing a mask is a necessary behavior”. The measurement for intention to wear masks was adapted from the research of Steffen et al ( 12 ) and included four items that appear in their study: “Based on the above statement about taking preventive measures, I decided to wear masks in public places,” “I would recommend my family and friends to wear masks,” “If the doctor/government suggests, I will strictly abide by the measures of wearing masks”, and “I intend to wear masks because it can block the spread of viruses”. The measurement for social norms was adapted from the research of Mir et al ( 37 ) and included four items that appear in their study: “My family suggested that I should wear a mask,” “My friends and colleagues influenced my decision to wear a mask,” “Important people influenced my decision to wear a mask”, and “The policy of epidemic prevention and control guidelines influenced my decision to wear a mask.” The measurement for information credibility was adapted from the research of Appelman ( 24 ) and Sundar ( 38 ) and mainly measures the accuracy, authenticity, and reliability of information through items such as “I think the above information is”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This positive change in attitudes is related to the positive emotion of happiness induced by body-mind unity framing. Therefore, framing impacts on how the audience perceives and responds to a message, and hence it is essentially a fast way to change attitudes and behaviors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher perceptions of travel intentions result in social distancing, hand hygiene and mask-wearing (Steffen & Cheng, 2021 ; Xu & Cheng, 2021 ). As part of the public health response, travel intentions motivate people to adhere to preventive behaviors such as keeping social distancing, washing hands and wearing masks (Bae & Chang, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%